Challenging Cognitive Control by Mirrored Stimuli in Working Memory Matching - Wirth, Maria; Gaschler, Robert (Frontiers in Psychology, 2017)
Cognitive conflict has often been investigated by placing automatic processing originating from learned associations in competition with instructed task demands. Here we explore whether mirror generalization as a congenital mechanism can be employed to create cognitive conflict. Past research suggests that the visual system automatically generates an invariant representation of visual objects and their mirrored counterparts (i.e., mirror generalization), and especially so for lateral reversals (e.g., a cup seen from the left side vs. right side). Prior work suggests that mirror generalization can be reduced or even overcome by learning (i.e., for those visual objects for which it is not appropriate, such as letters d and b). We, therefore, minimized prior practice on resolving conflicts involving mirror generalization by using kanji stimuli as non-verbal and unfamiliar material. In a 1-back task, participants had to check a stream of kanji stimuli for identical repetitions and avoid miss-categorizing mirror reversed stimuli as exact repetitions. Consistent with previous work, lateral reversals led to profound slowing of reaction times and lower accuracy in Experiment 1. Yet, different from previous reports suggesting that lateral reversals lead to stronger conflict, similar slowing for vertical and horizontal mirror transformations was observed in Experiment 2. Taken together, the results suggest that transformations of visual stimuli can be employed to challenge cognitive control in the 1-back task.